Gospel Melodies and Evangelistic Hymns - Review and Herald Publishing Association; Nang Chan Yeema (Hagerstown, MD USA Review and Herald Publishing Association, 1944)
This book is compiled especially for use in Evangelistic Meetings.
Keywords: Reference